2003
DOI: 10.1002/joc.873
|View full text |Cite
|
Sign up to set email alerts
|

Microclimate of a desert playa: evaluation of annual radiation, energy, and water budgets components

Abstract: We set up two automatic weather stations over a playa (the flat floor of an undrained desert basin that, at times, becomes a shallow lake), approximately 65 km east-west by 130 km north-south, located in Dugway (40°08 N, 113°27 W, 1124 m above mean sea level) in northwestern Utah, USA, in 1999. These stations measured the radiation budget components, namely: incoming R si and outgoing R so solar or shortwave radiation, using two Kipp and Zonen pyranometers (one inverted), the incoming R li (or atmospheric) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 14 publications
2
16
0
Order By: Relevance
“…On average over the period JJA at the four sites, G, H, and lE shared 6%, 73%, and 21% of R n , respectively. These percentages are similar to those recorded at desert playas by Malek et al (1990) and Malek (2003), while lE from relatively moist grassland is generally the major component, being approximately three-times greater than H (Betts et al, 1996).…”
Section: Article In Presssupporting
confidence: 80%
“…On average over the period JJA at the four sites, G, H, and lE shared 6%, 73%, and 21% of R n , respectively. These percentages are similar to those recorded at desert playas by Malek et al (1990) and Malek (2003), while lE from relatively moist grassland is generally the major component, being approximately three-times greater than H (Betts et al, 1996).…”
Section: Article In Presssupporting
confidence: 80%
“…Allison and Barnes, 1985;Ullman, 1985;Jacobson and Jankowski, 1989;Malek et al, 1990;Tyler et al, 1997;Menking et al, 2000;Malek, 2003) have found that evaporation rates are quite low, due to the high salinity of groundwater and soil moisture and to the formation of salt crusts that either limit capillary rise or form impermeable barriers to liquid water. Although only a few studies have been conducted on the energy budget characteristics of playas (Malek et al, 1990;Tyler et al, 1997;Menking et al, 2000;Malek, 2003), those measurements that exist show that playa salt crusts are particularly suited to inhibiting evaporation, for they reflect the incoming solar radiation that provides the energy source for evaporation and often represent a cap that can be highly resistant to water vapor transport (Malek et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Being remnants of previous close-basin lakes during previous wet palaeoclimate (Bowler et al, 1986;Magee et al, 1995) or ephemeral water bodies following occasional inundations (Handford, 1982;Magee et al, 1995), the playas are characterized by low organic matter (Bowler et al, 1986) and low-porosity fine-grained sediments, mainly consisting of silt and clay (Bowler et al, 1986). These flat fine-grained sediments characterized many of the arid and semi-arid regions of the world, reported, among other places, from the arid regions of the southwestern USA (Handford, 1982;Malek, 2003;Wondzell et al, 1990), the Sahara (Hamdi-Aissa et al, 2004;Schild and Wendorf, 2001), Namibia (Ward, 1988), China (Pachur and Wünnemann, 1995;Vengosh et al, 1995) and Australia (Bowler et al, 1986;Magee et al, 1995). In contrast to playa lakes which are wet >75% of the year, playas are defined as sediments which are dry >75% of the year (Briere, 2000).…”
Section: Introductionmentioning
confidence: 99%